1988
DOI: 10.1007/bf01794687
|View full text |Cite
|
Sign up to set email alerts
|

CSF-endorphines in acute and chronic brain lesions

Abstract: In order to answer the question of an opioid influence on consciousness, a radio-immuno-assay (n = 852) of beta-endorphin and beta-LPH (beta-lipotropic hormone) in both ventricular CSF and blood plasma was carried out in 101 neurosurgical patients. The following results were obtained: I) beta-END and beta-LPH levels were found to be lower in the CSF than in blood plasma. II) beta-END and beta-LPH in the CSF was the same in both sexes. III) beta-END levels in the CSF decreased with age. IV) beta-END and beta-LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These variations appeared to be due to the diversity of methods and experimental conditions involving stress, pain-related manipulations, and infections [111,113,116-118,120,129-133] . Another complicating factor is that β-END levels show diurnal fluctuations in plasma as well as in the CSF [134,135]. The conclusion is that CSF β-END concentration mostly exceeds peripheral β-END, which excludes the possibility that central levels are a passive reflection of peripheral levels.…”
Section: Central and Peripheral β-End Are Regulated Differentiallymentioning
confidence: 99%
“…These variations appeared to be due to the diversity of methods and experimental conditions involving stress, pain-related manipulations, and infections [111,113,116-118,120,129-133] . Another complicating factor is that β-END levels show diurnal fluctuations in plasma as well as in the CSF [134,135]. The conclusion is that CSF β-END concentration mostly exceeds peripheral β-END, which excludes the possibility that central levels are a passive reflection of peripheral levels.…”
Section: Central and Peripheral β-End Are Regulated Differentiallymentioning
confidence: 99%
“…According to the literature, CSF-BE levels are highest early in the morning, between 6 and 9 a.m. [13,103]. In the present thesis, all lumbar puncture on patients were done between 8 and 9 a.m., whereas the timing of lumbar puncture in healthy controls ranged from early morning to very early afternoon.…”
Section: Circadian Variationsmentioning
confidence: 82%
“…These destructive sites may also explain why the p-endorphin concentration in CSF was lower than in the plasma of control guinea pigs. Hamel (25) found that CSF p-endorphin concentrations in man were significantly lower than in plasma. These results support our findings of a lower 0-endorphin concentration in CSF as compared with plasma of guinea pigs.…”
Section: Discussionmentioning
confidence: 97%